First record of the Neolicaphrium recens Frenguelli, 1921 (Mammalia, Litopterna) in the Pleistocene of Santiago del Estero Province, Argentina - Gaudioso, Pablo J. (2017)
The first record of the Neolicaphrium recens Frenguelli, 1921 (Mammalia, Litopterna) from Pleistocene deposits of the Río Dulce, Rio Hondo Department, Santiago del Estero Province, Argentina, is reported. The morphology and morphometry observed in the specimen MPAT073 is coincident with the diagnostic characteristics of that species. This finding represents the northernmost and westernmost record of the species, and thus extends its geographical distribution. Geological data suggest that the material comes from a still unnamed Pleistocene stratigraphic unit. © 2017, Universidade de Sao Paulo. All rights reserved.